2004
DOI: 10.1080/10245330400010646
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Storage Time and Temperature on International Normalized Ratio (INR) Levels and Plasma Activities of Vitamin K Dependent Clotting Factors

Abstract: We designed this study to assess the effect of storage time and temperature on the international normalized ratio (INR) levels and plasma activities of vitamin K-dependent, clotting factors. A total of 100 subjects, comprising 34 healthy controls, 33 patients with liver cirrhosis and 33 patients on long-term coumarin therapy were enrolled. After centrifugation of collected specimens, aliquots of plasma were stored at room temperature (20 -22 degrees C), refrigerated at 2-6 degrees C and frozen at -40 degrees C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
1
18
1
Order By: Relevance
“…It has been advocated that the detected INR measurement remains unchanged if analyzed within 24 h (Adcock, Kressin & Marlar, 1998; McGlasson, 1999; Davis et al , 1998; Awad, Selim & Al‐Sabbagh, 2004; Rao et al , 2000; Froom et al , 2001; Brigden et al , 1997), whereas other studies have showed time‐dependent derangements of the measured INR (Kitchen et al , 2007; Van Geest‐Daalderop et al , 2005; Leeming et al , 1998). The published studies (Van Geest‐Daalderop et al , 2005; Davis et al , 1998; Awad, Selim and Al‐Sabbagh, 2004; Leeming et al , 1998; Adcock, Kressin and Marlar, 1998;McGlasson, 1999; Rao et al , 2000; Froom et al , 2001; Baglin & Luddington, 1997) suffer from various methodological shortcomings; e.g., small sample size (Rao et al , 2000; Froom et al , 2001) and simplified and insufficient statistical analyses (Baglin and Luddington, 1997; Froom et al , 2001; McGlasson, 1999) resulting in nonconclusive results (Bland & Altman, 2007). Noteworthy, the studies reporting on no alteration of the INR following a 24‐h storage of blood samples mainly focus on the effect on the overall mean INR, and thereby potentially missing changes in individual patients (Kitchen et al , 2007; Van Geest‐Daalderop et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It has been advocated that the detected INR measurement remains unchanged if analyzed within 24 h (Adcock, Kressin & Marlar, 1998; McGlasson, 1999; Davis et al , 1998; Awad, Selim & Al‐Sabbagh, 2004; Rao et al , 2000; Froom et al , 2001; Brigden et al , 1997), whereas other studies have showed time‐dependent derangements of the measured INR (Kitchen et al , 2007; Van Geest‐Daalderop et al , 2005; Leeming et al , 1998). The published studies (Van Geest‐Daalderop et al , 2005; Davis et al , 1998; Awad, Selim and Al‐Sabbagh, 2004; Leeming et al , 1998; Adcock, Kressin and Marlar, 1998;McGlasson, 1999; Rao et al , 2000; Froom et al , 2001; Baglin & Luddington, 1997) suffer from various methodological shortcomings; e.g., small sample size (Rao et al , 2000; Froom et al , 2001) and simplified and insufficient statistical analyses (Baglin and Luddington, 1997; Froom et al , 2001; McGlasson, 1999) resulting in nonconclusive results (Bland & Altman, 2007). Noteworthy, the studies reporting on no alteration of the INR following a 24‐h storage of blood samples mainly focus on the effect on the overall mean INR, and thereby potentially missing changes in individual patients (Kitchen et al , 2007; Van Geest‐Daalderop et al , 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of these theoretical advantages, sample preservation by liquid nitrogen is not carried out routinely in clinical laboratories due to lack of sufficient literature. Deep freezer compartment of refrigerator is not satisfactory for prolonged storage as it maintains temperature between À10 and À20°C; however, it is suitable for short-term storage [1]. Laboratories keep deep freeze but capital, maintenance, and electricity consumption costs of À70°C deep freeze are very high.…”
Section: Sirmentioning
confidence: 99%
“…Therefore 24h after VKA administration, factor X measurement should be preferred to monitor VKA efficiency. In addition to these benefits, clotting factors activities seem to be stable over storage time [32].…”
Section: Assessmentmentioning
confidence: 99%